The Effect of Drug Availability and Drug Prices on Patient Satisfaction at the K-24 Geliting Maumere Pharmacy Mediated by Waiting Time - Eldwin Laurenso Lomi; H. Purwadhi; Kahar Mulyani (Business Management, 2026)
Patient satisfaction is an important indicator in evaluating the quality of pharmacy services, as it reflects the effectiveness of services in meeting patient drug needs and expectations. However, this satisfaction is not only determined by drug availability and price, but also influenced by aspects of the service process, such as waiting time. This study aims to analyze the effect of drug availability and drug price on patient satisfaction, and to assess the role of waiting time as a mediating variable at Apotek K-24 Geliting Maumere. The research method used was a quantitative approach with multiple regression analysis and a mediation test. Data were obtained through distributing questionnaires to patients using pharmacy services. The results showed that drug availability significantly influenced patient satisfaction at Apotek K-24 Geliting Maumere. Adequate drug availability—in terms of quantity, completeness, and ease of obtaining drugs—makes patients feel helped, receive fast service, and perceive the pharmacy as more professional. In addition, drug price has also been shown to significantly influence patient satisfaction. When prices are considered reasonable, affordable, and in accordance with service quality, patients' positive perceptions of the pharmacy increase. Furthermore, the mediation test showed that waiting time strengthens the influence of drug availability and drug price on patient satisfaction. Medication availability and pricing are more optimal when supported by fast and efficient waiting times. Therefore, the combination of good medication availability, affordable prices, and optimal waiting times significantly contributes to improving overall patient satisfaction at Apotek K-24 Geliting Maumere.